2000
DOI: 10.1039/b003422n
|View full text |Cite
|
Sign up to set email alerts
|

Direct conversion of aromatics into a synthetic steamcracker feed using bifunctional zeolite catalysts

Abstract: Aromatics with 6 to 9 carbon atoms can be converted catalytically with hydrogen on bifunctional zeolites, such as Pd/H-ZSM-5, into a high-quality steamcracker feed, thereby opening a direct route for the utilisation of surplus pyrolysis gasoline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 7 publications
0
16
0
2
Order By: Relevance
“…A survey published by EPA showed that most of the refiners plan to install additional naphtha pre-fractionation capacities [2]. The catalytic conversion of aromatics as proposed by Weitkamp can be a competing technology [3]. Molecular sieving of n-alkane/aromatic mixtures by nanopore membranes in pervaporation or vapour permeation might be another competing technology to distillation.…”
Section: Introductionmentioning
confidence: 99%
“…A survey published by EPA showed that most of the refiners plan to install additional naphtha pre-fractionation capacities [2]. The catalytic conversion of aromatics as proposed by Weitkamp can be a competing technology [3]. Molecular sieving of n-alkane/aromatic mixtures by nanopore membranes in pervaporation or vapour permeation might be another competing technology to distillation.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] These molecular sieves are used not only in catalytic processes such as toluene alkylation, [6][7][8][9] disproportionation, and xylene isomerization, [5,[10][11][12][13] but also for hydrocarbon separation. [14] Shape-selective sorption and transport [10,15,16] of (substituted) aromatic molecules are the key zeolites properties for these applications.…”
mentioning
confidence: 99%
“…It has been demonstrated that there are two process options for achieving the desired conversion [81,82]. It has been demonstrated that there are two process options for achieving the desired conversion [81,82].…”
Section: Ring Opening Of Aromatics In Pyrolysis Gasoline Followed By mentioning
confidence: 99%
“…It was only after the introduction of bifunctional zeolite catalysts that a smooth and stable conversion of aromatics into a synthetic steam-cracker feed became feasible [82]. It was only after the introduction of bifunctional zeolite catalysts that a smooth and stable conversion of aromatics into a synthetic steam-cracker feed became feasible [82].…”
Section: Direct Ring Opening Of Aromatics On Bifunctional Zeolitesmentioning
confidence: 99%